Children in Harm's Way: a Global Issue as Important as Climate Change - Kendall, Garth; van Eekelen, J.; Mattes, E.; Li, Jianghong (Forum on Public Policy, 2009)
AbstractConsiderable evidence points to the importance of early development from the time of conception in causalpathways to life-long health and wellbeing. A consistent theme is evolving regarding the interplay betweenpsychological and social factors and biological mechanisms, such as genetic predisposition and stress-relatedneuroendocrine functioning. The focus of interest is the developing child and the emerging capacity for emotional,attentional, and social regulation. Of substantial importance is the possibility that the experience of multiple stressfullife-events within the family, school and community directly and indirectly influences these regulatory processes.Evidence suggests that the experience of life-stress modifies the child?s biology through the central mediator ofstress responsiveness, the hypothalamic-pituitary-adrenal (HPA) axis.Children in both developing and developed countries are at risk of poor health and developmental outcomes acrossthe lifespan. Terrorism, civil unrest, youth crime and violence, high rates of mental health problems in both childrenand adults, high rates of substance abuse, promiscuous sexual behaviour, and high rates of starvation as well asobesity are all symptoms of the underlying problem. While the causes are complex and involve an interplay betweenindividual, family and community characteristics, there is increasing evidence that supportive public policy across arange of portfolios is key to reversing this disturbing situation. Failure to act now, both nationally and globally,poses a dire risk for future human habitation arguably greater than the impact of unabated climate change.